2020
DOI: 10.1186/s12889-020-08602-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of health extension workers on drug provision for childhood illness in west Gojjam, Amhara, Northwest Ethiopia

Abstract: Background: The HEP was established decades ago to address preventive, promotive and selective curative services through Health Extension Workers (HEWs). However, knowledge and practice of HEWs on drug provision for childhood illnesses such as diarrhea, fever, and/or acute respiratory infection have not been well studied. This study aimed to assess the knowledge and practice of HEWs on drug provision for childhood illnesses. Methods: An institutional-based cross-sectional study was conducted among 389 rural HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Inadequate preparedness and low service quality at the primary healthcare level reduce parents’ trust and utilisation of health services 11 19–21. In Ethiopia, the low utilisation of iCCM services was also attributed to absent supervision and refresher training of health extension workers 22–27. We have earlier shown that a substantial proportion of caregivers were not aware of pneumonia-related health services and, therefore, less likely to seek care when their children got sick or get their children immunised 28 29.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate preparedness and low service quality at the primary healthcare level reduce parents’ trust and utilisation of health services 11 19–21. In Ethiopia, the low utilisation of iCCM services was also attributed to absent supervision and refresher training of health extension workers 22–27. We have earlier shown that a substantial proportion of caregivers were not aware of pneumonia-related health services and, therefore, less likely to seek care when their children got sick or get their children immunised 28 29.…”
Section: Introductionmentioning
confidence: 99%
“…We only have data from implementers' perspective, and it would be beneficial to have data from the HEWs themselves. In other studies, HEWs' lack of motivation has been due to a lack of skills and competing activities for which they were more closely monitored or supervised [35][36][37]. In line with this, a study that looked at implementation fidelity of initiatives to improve infant and young child feeding in Ethiopia reported that, while fidelity in the training of HEWs was high, gaps remained in cascading activities by HEWs to beneficiaries.…”
Section: Discussionmentioning
confidence: 94%
“…In the narratives, the male perception of a provider who spends his time working, ensuring the provision of food and clothing for his children contrasts with the necessity for interaction and, consequently, affective bonds, pointed out in studies in Brazil and Ethiopia, where gender stereotypes influence the male understanding of paternity and, therefore, describe models of paternal absence related to affective bonds (25)(26) . This perception of paternity, although not the only one existing in our society, is the most reported in other research and often the most reproduced among the male population.…”
Section: Percepção De Homens Perpetradores De Violência Acerca Da Pat...mentioning
confidence: 99%